Deep Skull from Niah Cave and the Pleistocene Peopling of Southeast Asia - Curnoe, Darren; Datan, Ipoi; Taçon, Paul S. C.; Leh Moi Ung, Charles; Sauffi, Mohammad S. (Frontiers in Ecology and Evolution, 2016)
The Deep Skull from Niah Cave in Sarawak (Malaysia) is the oldest anatomically modern human recovered from island Southeast Asia. For more than 50 years its relevance to tracing the prehistory of the region has been controversial. The most widely held view, originating with Brothwell’s 1960 description and analysis, is that the Niah individual is related to Indigenous Australians. Here we undertake a new assessment of the Deep Skull and consider its bearing on this question. In doing so, we provide a new and comprehensive description of the cranium including a reassessment of its ontogenetic age, sex, morphology and affinities. We conclude that this individual was most likely to have been of advanced age and female, rather than an adolescent male as originally proposed. The morphological evidence strongly suggests that the Deep Skull samples the earliest modern humans to have settled Borneo, most likely originating on mainland East Asia. We also show that the affinities of the specimen are most likely to be with the contemporary indigenous people of Borneo, although, similarities to the population sometimes referred to as Philippine Negritos cannot be excluded. Finally, our research suggests that the widely supported ‘two-layer’ hypothesis for the Pleistocene peopling of East/South Asia is unlikely to apply to the earliest inhabitants of northern Borneo, in-line with the picture emerging from genetic studies of the contemporary people from the region.